Perbandingan Perlindungan Hukum Merek antara Prinsip First to File Hukum Indonesia dan Prinsip First to Use pada Hukum Australia - Neisa Ines Tritanaya; Wiwin Yulianingsih (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2022)
Intellectual Property Rights are the exclusive rights to do something on the intellectual property, which is regulated by the norms or applicable laws. This study aims to determine the difference between the first to file principle in Indonesian law and the first to use principle in Australian law and to determine the strengths and weaknesses between the two principles. Indonesia adheres to a â€œfirst to fileâ€ system, which requires a trademark to be registered to obtain legal protection. While